Nursing of a patient with chronic obstructive pulmonary disease complicated with sleep apnea syndrome (1例慢性阻塞性肺疾病合并睡眠呼吸暂停综合征患者的护理) - GE Ruoxing (葛若星); JIANG Ying (姜英) (中西医结合护理)
This paper summarized the nursing management of a patient with chronic obstructive pulmonary disease complicated with sleep apnea syndrome. Based on Orem's self-care nursing theory, targeted interventions according to the different stage of disease were carried out to improve the self-care ability of the patient, as well as preventing complications and improving the quality of life. (本文总结1例慢性阻塞性肺疾病(COPD)合并睡眠呼吸暂停综合征患者的护理经验。基于Orem自护理论, 根据患者疾病不同时期进行针对性护理, 以提高患者自护能力, 预防并发症, 改善患者症状, 提高其生活质量。)